Resistência ao Cisalhamento de um Latossolo sob Diferentes uso e Manejo - Silva, Reginaldo Barboza da [UNESP]; Dias Junior, M. S.; Santos, F. L.; Franz, C. A B (FapUNIFESP (SciELO), 2004)
Shear soil strength is an important dynamic property of the soil, as well as the state of soil consistence concerning the structure behavior of agricultural soils, which are mostly being ignored in research into the influence of use and management. This fact has been contributing to the perennial problem of fallacious strategies, causing degradation of the physical and mechanical soil properties. This study aimed at an evaluation of the shear soil strength of a dystrophic Red Latosol submitted to conventional tillage, direct seeding, and Cerrado as control treatment, with different water contents: 0.05; 0.16; 0.18, and 0.38 kg kg -1. Results allowed the conclusion that the shear strength of the soil, appraised at a depth of 0-0.05 m of a dystrophic Red Latosol, was affected by water content increases, use and management type. In general, the adjusted equations according to the Coulomb model evidenced greater shear strength in the Cerrado, followed by conventional tillage, and direct seeding. The lowest shear strength of the studied soil, corroborated by the smallest internal friction angle (tg φ) and larger apparent cohesion (c), specifically for the water content 0.16 and 0.27 kg kg -1 (contemplating, therefore, the friable range of the soil), pointed to direct seeding as the management with the greatest possibilities of preserving the structural sustainability of the soil studied. The prediction of shear tension proved to be sensitive to the effects of soil water variations and the use type. This enables significant contributions, particularly to studies on the structural sustainability of agricultural soils, which are usually impaired by inadequate traffic and tillage operations.
Shear strength of a latosol under different use and management
Keywords: Latossol; Soil management; Structural sustainability